Collective leadership among Malaysian secondary school teachers - Sivalingam, Shiveh; Abdul Kadir, Suhaida; Asimiran, Soaib (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
To date the increasing trend in the teaching fraternity is moving towards one where members of an educational institution play a managerial role. The term given to this style of leading is collective leadership and it is given immense importance in the Malaysian Education Blueprint 2013-2025 which states that the system is moving towards having every participating member in a school to have greater share in decision making. This paper studies collective leadership by demography on Malaysian secondary schools in Kuala Lumpur. The results show that there is no significant difference between gender as well as subjects and collective leadership, nonetheless, teachers with higher education and those who taught lower secondary levels had higher efficacy in collective leadership.